1998
DOI: 10.1002/(sici)1096-9861(19980525)395:1<18::aid-cne2>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Timed markers for the differentiation of the cuticular plate and stereocilia in hair cells from the mouse inner ear

Abstract: The differentiation of the cuticular plate and stereocilia in cochleovestibular hair cells from the mouse was traced with monoclonal antibodies raised by in vitro immunization. The cuticular plate is detected first from embryonic days 14-15 (E14-E15), before cell differentiation is apparent, either with scanning electron microscopy or with actin filament labeling. A flat disc of material forms beneath the apical membrane and subsequently expands, forming a fully shaped cuticular plate at postnatal stages 3-5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We have determined the peak expression period of the Tmhs gene to be between P0 and P3; it is slightly reduced at P6 and can no longer be detected at P15. This period of expression coincides with the period of stereocilia maturation (Nishida et al 1998;Mburu et al 2006). Hair bundles in Tmhs mutant mice begin to degenerate by P8 (Longo-Guess et al 2005), which is about the same time that Tmhs expression ceases.…”
Section: Discussionmentioning
confidence: 81%
“…We have determined the peak expression period of the Tmhs gene to be between P0 and P3; it is slightly reduced at P6 and can no longer be detected at P15. This period of expression coincides with the period of stereocilia maturation (Nishida et al 1998;Mburu et al 2006). Hair bundles in Tmhs mutant mice begin to degenerate by P8 (Longo-Guess et al 2005), which is about the same time that Tmhs expression ceases.…”
Section: Discussionmentioning
confidence: 81%
“…We studied the distribution of harmonin during the period of hair bundle differentiation in the mouse and rat. In the mouse, stereocilia sprout from the apical surface of vestibular and cochlear hair cells at E13 and E15, respectively (Nishida et al ., 1998; Denman‐Johnson and Forge, 1999). In the cochlea, hair cell differentiation proceeds from the base to the cochlear apex and, by P4–P6, the hair bundles reach their final adult shape (Nishida et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In the mouse, stereocilia sprout from the apical surface of vestibular and cochlear hair cells at E13 and E15, respectively (Nishida et al ., 1998; Denman‐Johnson and Forge, 1999). In the cochlea, hair cell differentiation proceeds from the base to the cochlear apex and, by P4–P6, the hair bundles reach their final adult shape (Nishida et al ., 1998). A previous analysis of harmonin transcripts (see Figure 1A) has indicated that class b isoforms are restricted largely to the inner ear, whereas a and c forms have a much broader expression throughout the entire organism (Verpy et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Cultures fixed with 4% paraformaldehyde were labeled with antibodies to glial fibrillary acid protein (GFAP, Sigma, G-A-5), OC P-2 (gift of R. Thalmann, Washington University, St. L ouis, MO), calretinin (AB149, Chemicon, Harrow, UK), parvalbumin (PA235, Sigma), ␤-tubulin [E7, Developmental Studies Hybridoma Bank (DSHB), University of Iowa], pan-fimbrin (737.4, gift of P. Matsudaira, Whitehead Institute for Biomedical Research, C ambridge, M A), Brn3.1 (PRB249C Babco, Berkeley, CA), and Z O-1 (R26.4c, DSHB, University of Iowa). Those fixed with a 1:1 mixture of acetone/methanol on ice were labeled with antibodies to occludin (71-1500 Zymed, San Francisco), pan-cytokeratin (C2562, Sigma,), vimentin (Vim13.2, Sigma), neurofilaments (200 kDa, Sigma, N4142; 165 kDa, 2H3, DSHB; 68 kDa, E1.9, DSHB), T antigen (Ab419; gift of Dr. P. Jat, L udwig Institute for C ancer Research, L ondon), and a range of our own monoclonal antibodies to hair cells (UB/C P1, UB/SC1, UB/SP1-3) (Nishida et al, 1998). After overnight incubation at 4°C, antibody binding was visualized using FI TC -conjugated goat anti-rabbit Ig (Sigma), FI TC -conjugated goat anti-mouse IgM (Sigma), and lissamine rhodamine-conjugated goat anti-mouse IgG (Jackson Immunoresearch Labs, West Grove, PA).…”
Section: Methodsmentioning
confidence: 99%